G241 Vitamin D levels in children and adolescents with cancer. (7th April 2014) - Ryan, JR; Shankar, A; Brain, C; Kagalwala, F; Say, J
Abstract : Aim: To assess blood vitamin D levels at time of cancer diagnosis in children, to supplement vitamin D where necessary, and reassess levels after 6 months of treatment. Methods: Newly diagnosed children had vitamin D, calcium [Ca], phosphate [P04] and parathyroid hormone (PTH) levels checked. Vitamin D deficiency was defined as a serum 25-hydroxyvitamin D (25[OH]D) level of less than 50nmol/L, and vitamin D insufficiency was defined as a 25[OH]D level of between 50–75 nmol/L. Children with levels <50 nmol/L were given cholecalciferol (6000 units/day >10 years, 3000 units/day <10 years) while children with levels between 50–75 nmol/L received a lower dose (2000 units/day >10 years, 1000 units/day <10 years). Vitamin D levels were rechecked after 6 months in all patients. Results: Forty-four children (31 male, 13 female) aged between 4 to 19 years are the subjects of this report. Twenty-six children were Caucasian and 18 were of Asian/African ethnicity. Only 16% [n = 7] of children had normal Vitamin D levels at diagnosis. The remaining 84% had either severe deficiency [n = 28; 64%] or insufficiency [n = 9; 20%]. Mean vitamin D levels in Caucasian children were 54nmol/L compared to 35 nmol/L (p < 0.05) in African/Asian children. 50% [n = 13/26] of Caucasian children were considered vitamin D deficient vs. 78% [n = 14/18] of children of Asian or African ethnicity [p < 0.05] There was no seasonal variation in the mean vitamin D levels; 44.6 nmol/L in Autumn/Winter vs. 47.8 nmol/L in Spring/Summer. Of those with vitamin D <50 nmol/L, 3 had serum PO4 <0.89 and high PTH levels. In 2 children, with vitamin D <75 nmol/L, Ca was <2.15 nmol/L. Of the six children who have had 6 months of vitamin D supplementation, levels have normalised in four children [5/7 required treatment doses], and improved but not normalised in two children. One child who had normal vitamin D level at diagnosis has become deficient at 6 months [vitamin D <50 nmol/L]. Conclusion: The majority of our children were vitamin D deficient at diagnosis with significantly lower levels in African/Asian children. Derangement of PTH, calcium or phosphate was rare.